High-temperature-resistant carbon / ceramic gradient composite material brake pad as well as preparation method and application thereof
By adopting high-temperature resistant carbon/ceramic gradient composite brake pads, combined with chemical vapor deposition and directional reaction seepage technology, the safety hazards and poor heat conduction caused by heat increase during high-energy braking are solved, and the brake pads are achieved with high temperature resistance, low heat conduction, low wear and stable friction coefficient, improving the safety and reliability of the brake system.
Patent Information
- Application Number
- CN202510370037.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
During the high-energy braking process, traditional brake pads cause friction materials to decompose, reduce friction coefficient and abnormal wear due to heat increase, causing braking safety hazards and poor heat conduction, threatening the safety and reliability of the brake system.
High-temperature resistant carbon/ceramic gradient composite brake pads are used, which are composed of carbon/ceramic gradient composite friction sheets, composite heat insulation sheets, metal back plates and rivets. The structure is formed by rivet rivets, and gradient composite materials are prepared by chemical vapor deposition and directional reaction seepage and other technologies are introduced to improve friction stability.
The brake pads are achieved with high temperature resistance, low heat conduction, low wear and stable friction coefficient, improving the braking safety performance of special vehicles, heavy-duty cars, sports cars, etc., and ensuring the friction surface integrity and life of carbon/ceramic brake discs.
Smart Images

Figure CN119878738A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of brake pads, and in particular relates to a high-temperature resistant carbon / ceramic gradient composite brake pad and a preparation method and application thereof. Background Art
[0002] Carbon / ceramic composite brake discs can significantly reduce the unsprung mass of a vehicle and improve its fuel efficiency due to their advantages such as light weight, strong temperature resistance and no thermal decay. They also have the characteristics of long service life and low maintenance cost. They have become the preferred choice for high-energy braking of the new generation of lightweight vehicles and have broad market application prospects in special vehicles, heavy-duty vehicles, sports cars and passenger cars.
[0003] Driven by the automotive industry, the market application of carbon / ceramic brake discs is in an explosive growth trend, but traditional brake pad materials can no longer meet the comprehensive performance requirements of high-energy braking of automobiles. During the high-energy braking process of automobiles, the heat generated by the friction between traditional brake pads and carbon / ceramic brake discs will cause the working temperature of the brake pads to rise sharply, causing the decomposition or even combustion of organic matter or other substances in traditional friction materials, and at the same time causing a significant decrease in the friction coefficient and abnormal wear of the brake pads, causing a series of braking safety hazards. In addition, the heat generated by high-energy braking will be quickly transmitted to the surrounding environment of the brakes such as the piston through the brake pads, seriously threatening the safety and reliability of the entire braking system. In view of the limitations of the use of traditional brake pads with carbon / ceramic brake discs in high-temperature braking environments, the current market urgently needs a new type of brake pad that is both resistant to high temperatures, low wear, low heat conduction, and matches the friction coefficient of carbon / ceramic brake discs to meet the high-energy braking needs of special vehicles, heavy-duty vehicles, sports cars, etc. equipped with carbon / ceramic brake discs and improve the safety of the corresponding braking system. Summary of the invention
[0004] The purpose of the present invention is to provide a high temperature resistant carbon / ceramic gradient composite brake pad and a preparation method and application thereof.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-temperature resistant carbon / ceramic gradient composite brake pad, the brake pad comprising a carbon / ceramic gradient composite friction pad, a composite thermal insulation pad, a metal back plate and rivets; the carbon / ceramic gradient composite friction pad, the composite thermal insulation pad and the metal back plate are riveted together, and the composite thermal insulation pad is located between the carbon / ceramic gradient composite friction pad and the metal back plate.
[0006] Among them, the preparation method of the carbon / ceramic composite gradient friction plate is as follows: after the carbon fiber preform is subjected to a high-temperature heat treatment, the carbon fiber preform is pyrolyzed and carbon densified by chemical vapor deposition, and then it is impregnated and cured with a composite resin and subjected to a secondary high-temperature heat treatment to obtain a composite material blank, and finally a gradient-distributed ceramic phase is introduced by directional reaction infiltration.
[0007] Furthermore, the carbon fiber preform adopts an integral needle felt structure, and the volume content of carbon fiber is 20-30%. The method of high temperature heat treatment of the carbon fiber preform is: in an argon protective atmosphere, the carbon fiber preform is treated at a high temperature environment of 1800-2100°C for 0.5-2h.
[0008] Furthermore, chemical vapor deposition uses gaseous hydrocarbons as carbon source precursors and nitrogen as diluent gas, and introduces pyrolytic carbon matrix into the internal pores of the preform by cracking hydrocarbons at 900-1100°C, with a total deposition time of 100-200 hours.
[0009] The gaseous hydrocarbons may be propylene, natural gas, or mixed gases such as natural gas + propylene, natural gas + propane, etc. Under the mixed gas conditions, propylene and propane are added in small amounts, and the natural gas process may be referred to.
[0010] Furthermore, the gaseous hydrocarbon uses propylene, the flow ratio of propylene to nitrogen is 3:1-2:1, and the deposition pressure is 0.6-1.5kPa; the gaseous hydrocarbon uses a natural gas + propylene mixed gas, the flow ratio of natural gas to propylene is 10:1-20:1, and the deposition pressure is 2-5kPa.
[0011] Furthermore, the apparent density of the porous carbon / carbon composite material obtained by introducing the carbon fiber preform into the pyrolyzed carbon matrix by chemical vapor deposition is 1.10-1.30 g / cm 3 ; Furthermore, the composite resin is prepared by mixing furfural resin, phosphoric acid and nano powder, and the nano powder is selected from one or more of nano silicon powder and nano carbide powder; the specific preparation method of the composite resin is as follows: (1) mixing furfural resin and polysilicon boroxane in a weight ratio of (12-15):1, adjusting the pH to 3-3.5 with acetic acid, and reacting at 85-90°C for 4-6 hours to obtain a modified furfural resin; (2) Phosphoric acid accounting for 6-9 wt % of the modified furfural resin and nano powder accounting for 3-5 wt % of the modified furfural resin are added to the modified furfural resin and mixed evenly to obtain a composite resin.
[0012] The inventor tried to use commercially available furfural resin as an organic resin for impregnation, but after the introduction of the pyrolytic carbon matrix, the impregnation uniformity of the porous carbon / carbon blank was poor and the compatibility with the nanopowder was poor, and the dispersibility of the nanopowder particles was not ideal. The present invention modifies the commercially available furfural resin, improves the distribution uniformity of the nanopowder in the material, and thus improves the friction stability of the brake pad. It is inferred through analysis that polysilicon boroxane improves the chemical affinity and surface energy of the furfural resin to a certain extent, and the BO bond with a higher internal bond energy can improve the fluidity of the furfural resin by affecting the structure of the furfural resin, significantly improves the impregnation effect of the composite resin and the distribution uniformity of the nanoparticles, and thus effectively improves the friction stability of the brake pad.
[0013] Furthermore, the nano powder is a compound of nano carbide powder and nano silicon powder in a weight ratio of (2-3):1.
[0014] Furthermore, the nano carbide powder is one or both of silicon carbide powder and zirconium carbide powder.
[0015] Furthermore, the nano carbide powder is silicon carbide powder.
[0016] Furthermore, the composite resin is infiltrated into the porous carbon / carbon composite material by impregnation under a certain pressure, and a composite material blank is obtained after curing and secondary heat treatment.
[0017] Furthermore, the composite resin impregnation pressure is 2-4 MPa, and the impregnation time is 4-6 h.
[0018] Furthermore, the curing temperature after composite resin impregnation is 180-220°C, and the curing time is 2 hours.
[0019] Furthermore, the secondary high temperature heat treatment temperature is 1800-2300°C and the time is 1-3h.
[0020] Furthermore, the apparent density of the composite body is 1.25-1.45 g / cm 3 .
[0021] Furthermore, the specific operation of directional reaction infiltration is as follows: using a certain amount of silicon powder as the infiltration material, firstly flatten and compact the infiltration material on the bottom of the graphite crucible, then place the composite material blank on top of the infiltration material, heat it to 1800-2000°C under the protection of inert gas, and keep it warm for 1-3h to obtain a carbon / ceramic composite material blank.
[0022] Furthermore, the silicon powder has a particle size of 80-100 mesh.
[0023] Furthermore, the volume density of the obtained carbon / ceramic composite material showed a gradient distribution characteristic; the density of the composite material area close to the infiltration material was 2.0-2.2 g / cm 3 , used to provide sufficient riveting connection strength; the density of the composite area away from the infiltration material is 1.7-1.9g / cm 3 , has a certain compressibility and is used to meet the comprehensive friction performance requirements of the friction plate.
[0024] The composite material heat insulation sheet is a high-silicon composite material or a quartz fiber composite material, and is made into a thin sheet by machining.
[0025] Further, the thickness of the composite thermal insulation sheet is 2-3 mm; Furthermore, the use of high-silica composite materials as thermal insulation sheets can meet the brake pad's extreme operating temperature requirement of 800°C; the use of quartz fiber composite materials can meet the brake pad's extreme operating temperature requirement of 1500°C.
[0026] The composite material blank is processed to obtain a carbon / ceramic gradient composite material friction plate, which is then stacked with a composite material heat insulation plate and a steel back, and effectively riveted by rivets to obtain a carbon / ceramic gradient composite material brake pad.
[0027] Furthermore, the carbon / ceramic gradient composite brake pad is composed of two carbon / ceramic composite friction pads, two composite heat insulation pads, an integral steel back and 8 rivets.
[0028] The present invention provides a high temperature resistant carbon / ceramic gradient composite brake pad prepared by the above-mentioned preparation method.
[0029] The present invention also provides the application of the high temperature resistant carbon / ceramic gradient composite brake pads prepared by the preparation method, which are applied to special vehicles, heavy-duty vehicles, sports cars, passenger cars and the like that use carbon / ceramic brake discs.
[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention provides a high temperature resistant carbon / ceramic gradient composite brake pad and its preparation method and application. The prepared brake pad is specially used for carbon / ceramic brake discs, has the advantages of high temperature resistance, low heat conduction, low wear and stable friction coefficient, and can be used to improve the braking safety performance of special vehicles, heavy-duty vehicles, sports cars, passenger cars, etc.; 2. The present invention modifies the commercially available furfural resin to obtain a composite resin with uniform nanopowder distribution. The introduction of a uniform ceramic phase in the resin carbon matrix can effectively improve the friction coefficient stability of the brake pad and the profile stability of the friction surface; 3. The present invention designs and realizes the gradient structure and function of the carbon / ceramic friction pad, which, on the one hand, improves the overall structural reliability and stability of the carbon / ceramic gradient composite material brake pad with riveted structural characteristics; on the other hand, it simultaneously ensures the compressibility of the carbon / ceramic friction surface, as well as the reliability and stability of the friction performance with the carbon / ceramic brake disc, avoids braking damage to the carbon / ceramic brake disc surface, and ensures the integrity and life of the carbon / ceramic brake disc friction surface; 4. The friction functional surface area of the carbon / ceramic composite friction plate of the present invention is composed of carbon fiber, pyrolytic carbon matrix, resin carbon matrix containing carbide particles and silicon carbide matrix with continuous network structure. The above multi-component composition synergistically endows the brake pad with a relatively stable friction coefficient and low wear amount; 5. The present invention introduces a composite heat insulation sheet between the friction plate and the steel back, thereby effectively reducing the energy transfer of heat generated by high-energy braking to the surrounding environment of the braking system, greatly improving the safety and reliability of the braking system. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a structural diagram of a high temperature resistant carbon / ceramic gradient composite brake pad; Figure 2 This is a physical picture of the high-temperature resistant carbon / ceramic gradient composite brake pad product. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1: like Figure 1-2 As shown, this embodiment provides a high temperature resistant carbon / ceramic gradient composite brake pad, which comprises a carbon / ceramic gradient composite friction plate, a composite thermal insulation plate, a metal back plate and rivets; the carbon / ceramic gradient composite friction plate, the composite thermal insulation plate and the metal back plate are riveted together by rivets, and the composite thermal insulation plate is located between the carbon / ceramic gradient composite friction plate and the metal back plate.
[0034] Among them, the preparation method of the carbon / ceramic composite gradient friction plate is as follows: after the carbon fiber preform is subjected to a high-temperature heat treatment, the carbon fiber preform is pyrolyzed and carbon densified by chemical vapor deposition, and then it is impregnated and cured with a composite resin and subjected to a secondary high-temperature heat treatment to obtain a composite material blank, and finally a gradient-distributed ceramic phase is introduced by directional reaction infiltration.
[0035] The carbon fiber preform adopts an integral needle felt structure, and the volume content of carbon fiber is 23%. The method of high temperature heat treatment of the carbon fiber preform is: in an argon protective atmosphere, the carbon fiber preform is treated at a high temperature environment of 2000°C for 1 hour.
[0036] Chemical vapor deposition uses gaseous hydrocarbons as carbon source precursors and nitrogen as diluent gas. The pyrolytic carbon matrix is introduced into the internal pores of the preform by cracking the hydrocarbons at 980°C. The total deposition time is 150 hours.
[0037] The gaseous hydrocarbon used was propylene, the flow ratio of propylene to nitrogen was 2:1, and the deposition pressure was 0.8 kPa; The apparent density of the porous carbon / carbon composite material obtained by introducing the carbon fiber preform into the pyrolyzed carbon matrix through chemical vapor deposition is 1.16 g / cm 3 ; The composite resin is prepared by mixing furfural resin, phosphoric acid and nano powder; the specific preparation method of the composite resin is as follows: (1) Mixing furfural resin and polysilicon boroxane in a weight ratio of 13:1, adjusting the pH to 3.2 with acetic acid, and reacting at 88°C for 5 hours to obtain a modified furfural resin; (2) Phosphoric acid accounting for 7 wt.% of the modified furfural resin and nanopowder accounting for 4 wt.% of the modified furfural resin were added to the modified furfural resin and mixed evenly to obtain a composite resin.
[0038] Furfuryl ketone resin: purchased from Zhejiang Tianqi New Materials Technology Co., Ltd., brand FA-2.
[0039] The nano powder is a mixture of nano carbide powder and nano silicon powder (Shanghai Maoguo Nano Technology Co., Ltd., MG-Si-100) in a weight ratio of 3:1.
[0040] The nano carbide powder is silicon carbide powder (Beijing Dekedaojin Technology Co., Ltd., DK-SiC-001).
[0041] The composite resin is infiltrated into the porous carbon / carbon composite material by impregnation under a certain pressure, and a composite material blank is obtained after curing and secondary heat treatment.
[0042] The composite resin impregnation pressure was 3 MPa and the impregnation time was 5 h.
[0043] After composite resin impregnation, the curing temperature was 200°C and the curing time was 2h.
[0044] The secondary high temperature heat treatment temperature is 2000℃ and the time is 2h.
[0045] The apparent density of the composite body is 1.38 g / cm 3.
[0046] The specific operation of directional reactive infiltration is as follows: a certain amount of silicon powder is used as the infiltration material, the infiltration material is first flattened and compacted on the bottom of the graphite crucible, and then the composite material blank is placed on top of the infiltration material, and the temperature is raised to 1900°C under the protection of inert gas, and the heat preservation treatment is carried out for 2 hours to obtain a carbon / ceramic composite material blank.
[0047] The silicon powder has a particle size of 80-100 meshes.
[0048] The volume density of the obtained carbon / ceramic composite material showed a gradient distribution characteristic; the density of the composite material area close to the infiltration material was 2.19 g / cm 3 , used to provide sufficient riveting connection strength; the density of the composite material area away from the infiltration material is 1.86g / cm 3 , has a certain compressibility and is used to meet the comprehensive friction performance requirements of the friction plate.
[0049] The composite material heat insulation sheet is a high-silicon-oxygen composite material and is made into a thin sheet by machining.
[0050] High silica composite material: purchased from Xi'an Kangben Materials Co., Ltd.
[0051] The thickness of the composite thermal insulation sheet is 3 mm; Using high-silicon-oxygen composite materials as thermal insulation sheets can meet the brake pad's extreme operating temperature requirement of 800°C.
[0052] The composite material blank is processed to obtain a carbon / ceramic gradient composite material friction plate, which is then stacked with a composite material heat insulation plate and a steel back, and effectively riveted by rivets to obtain a carbon / ceramic gradient composite material brake pad.
[0053] The carbon / ceramic gradient composite brake pad is composed of two carbon / ceramic composite friction pads, two composite heat insulation pads, an integral steel back and 8 rivets.
[0054] Embodiment 2: The present embodiment provides a method for preparing a high-temperature resistant carbon / ceramic gradient composite brake pad, which comprises a carbon / ceramic gradient composite friction pad, a composite thermal insulation pad, a metal back plate and rivets; the carbon / ceramic gradient composite friction pad, the composite thermal insulation pad and the metal back plate are riveted together, and the composite thermal insulation pad is located between the carbon / ceramic gradient composite friction pad and the metal back plate.
[0055] Among them, the preparation method of the carbon / ceramic composite gradient friction plate is as follows: after the carbon fiber preform is subjected to a high-temperature heat treatment, the carbon fiber preform is pyrolyzed and carbon densified by chemical vapor deposition, and then it is impregnated and cured with a composite resin and subjected to a secondary high-temperature heat treatment to obtain a composite material blank, and finally a gradient-distributed ceramic phase is introduced by directional reaction infiltration.
[0056] The carbon fiber preform adopts an integral needle felt structure, and the volume content of carbon fiber is 30%. The method of high temperature heat treatment of the carbon fiber preform is: in an argon protective atmosphere, the carbon fiber preform is treated at a high temperature environment of 1800°C for 2 hours.
[0057] Chemical vapor deposition uses gaseous hydrocarbons as carbon source precursors and nitrogen as diluent gas. The pyrolytic carbon matrix is introduced into the internal pores of the preform by cracking the hydrocarbons at 1050°C. The total deposition time is 200h.
[0058] The gaseous hydrocarbons used were natural gas + propylene mixed gas, the flow ratio of natural gas to propylene was 20:1, and the deposition pressure was 2 kPa.
[0059] The apparent density of the porous carbon / carbon composite material obtained by introducing the carbon fiber preform into the pyrolyzed carbon matrix through chemical vapor deposition is 1.28g / cm 3 ; The composite resin is prepared by mixing furfural resin, phosphoric acid and nanopowder; The specific preparation method of the composite resin is as follows: (1) Mixing furfural resin and polysilicon boroxane in a weight ratio of 12:1, adjusting the pH to 3 with acetic acid, and reacting at 90°C for 4 hours to obtain a modified furfural resin; (2) Phosphoric acid accounting for 9 wt.% of the modified furfural resin and nanopowder accounting for 3 wt.% of the modified furfural resin were added to the modified furfural resin and mixed evenly to obtain a composite resin.
[0060] Furfuryl ketone resin: purchased from Zhejiang Tianqi New Materials Technology Co., Ltd., brand FA-2.
[0061] The nano powder is a mixture of nano carbide powder and nano silicon powder (Shanghai Maoguo Nano Technology Co., Ltd., MG-Si-100) in a weight ratio of 2:1.
[0062] The nano carbide powder is silicon carbide powder (Beijing Dekedaojin Technology Co., Ltd., DK-SiC-001).
[0063] The composite resin is infiltrated into the porous carbon / carbon composite material by impregnation under a certain pressure, and a composite material blank is obtained after curing and secondary heat treatment.
[0064] The composite resin impregnation pressure was 4 MPa and the impregnation time was 4 h.
[0065] The curing temperature after composite resin impregnation was 220°C and the curing time was 2h.
[0066] The secondary high temperature heat treatment temperature is 1800℃ and the time is 3h.
[0067] The apparent density of the composite body is 1.43 g / cm 3 .
[0068] The specific operation of directional reactive infiltration is as follows: a certain amount of silicon powder is used as the infiltration material, the infiltration material is first flattened and compacted on the bottom of the graphite crucible, and then the composite material blank is placed on top of the infiltration material, and the temperature is raised to 2000°C under the protection of inert gas, and the heat preservation treatment is carried out for 1 hour to obtain a carbon / ceramic composite material blank.
[0069] The silicon powder has a particle size of 80-100 meshes.
[0070] The volume density of the obtained carbon / ceramic composite material showed a gradient distribution characteristic; the density of the composite material area close to the infiltration material was 2.03g / cm 3 , used to provide sufficient riveting connection strength; the density of the composite material area away from the infiltration material is 1.72g / cm 3 , has a certain compressibility and is used to meet the comprehensive friction performance requirements of the friction plate.
[0071] The composite material heat insulation sheet is a quartz fiber composite material.
[0072] Quartz composite materials: purchased from Shandong Industrial Ceramics Design Institute Co., Ltd.
[0073] The thickness of the composite thermal insulation sheet is 2.3mm; the use of quartz fiber composite materials can meet the brake pad's extreme operating temperature requirement of 1500°C.
[0074] The composite material blank is processed to obtain a carbon / ceramic gradient composite material friction plate, which is then stacked with a composite material heat insulation plate and a steel back, and effectively riveted by rivets to obtain a carbon / ceramic gradient composite material brake pad.
[0075] The carbon / ceramic gradient composite brake pad is composed of two carbon / ceramic composite friction pads, two composite heat insulation pads, an integral steel back and 8 rivets.
[0076] Comparative Example 1: The difference between this comparative example and Example 1 is: The specific preparation method of the composite resin is as follows: 7 wt.% of phosphoric acid and 4 wt.% of nano powder are uniformly mixed in unmodified furfural resin to obtain the composite resin. Furfural resin: purchased from Zhejiang Tianqi New Materials Technology Co., Ltd., brand FA-2.
[0077] Comparative Example 2: The difference between this comparative example and Example 1 is that the nano powder is silicon carbide powder (Beijing Dekedaojin Technology Co., Ltd., DK-SiC-001).
[0078] Comparative Example 3: The difference between this comparative example and Example 2 is that the specific operation of directional reaction infiltration is to use excess silicon powder as the infiltration material, firstly flatten and compact the infiltration material on the bottom of the graphite crucible, then place the composite material blank on the top of the infiltration material, heat it to 2000°C under the protection of inert gas, and keep it warm for 1 hour to obtain the carbon / ceramic composite material blank; The volume density of the obtained carbon / ceramic composite material has no obvious gradient distribution characteristics; the density of the composite material area close to the infiltration material is 2.08g / cm 3 The density of the composite area away from the infiltration material is 2.02g / cm 3 .
[0079] Comparative Example 4: The difference between this comparative example and Example 2 is that the particle size of the silicon powder used as the infiltration material in the directional reactive infiltration process is 200 mesh.
[0080] Performance Test: The brake pads prepared in Examples 1-2 and Comparative Examples 1-4 were subjected to performance tests.
[0081] Test method: SAEJ2522, AKMaster.
[0082] Table 1 Performance test results:
[0083] The results show that the brake pads prepared in Examples 1-2 of the present invention have excellent comprehensive performance, and the performance matching decreases to varying degrees when the preparation conditions are changed.
[0084] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high temperature resistant carbon / ceramic gradient composite brake pad, characterized in that: The brake pad is made of a carbon / ceramic gradient composite friction pad, a composite heat insulation pad and a metal back plate riveted together by rivets, and the composite heat insulation pad is located between the carbon / ceramic gradient composite friction pad and the metal back plate; The preparation method of the carbon / ceramic gradient composite friction plate is as follows: subjecting a carbon fiber preform to a high-temperature heat treatment, then subjecting the carbon fiber preform to pyrolysis carbon densification by chemical vapor deposition, then subjecting the preform to composite resin impregnation and curing, then subjecting the preform to a secondary high-temperature heat treatment to obtain a composite material blank, and finally introducing a gradient-distributed ceramic phase by directional reaction infiltration; The carbon fiber preform is a needle-punched integral felt structure with a fiber volume content of 20-30%. The first high-temperature heat treatment is performed at 1800-2100°C for 0.5-2h in an argon protective atmosphere. The composite resin is infiltrated into the porous carbon / carbon composite material by impregnation, and a composite material body is obtained after curing and secondary heat treatment; The composite resin is prepared by mixing modified furfural resin, phosphoric acid and nano powder.
2. The method for preparing the high temperature resistant carbon / ceramic gradient composite brake pad according to claim 1, characterized in that: Chemical vapor deposition uses gaseous hydrocarbons as carbon source precursors. Under the deposition conditions of 900-1100℃, a pyrolytic carbon matrix is introduced into the carbon fiber preform after a single heat treatment. The apparent density of the obtained porous carbon / carbon composite material is 1.10-1.30g / cm 3 .
3. The method for preparing the high temperature resistant carbon / ceramic gradient composite brake pad according to claim 2, characterized in that: The preparation method of composite resin is as follows: (1) mixing furfural resin and polysilicon boroxane in a weight ratio of (12-15):1, adjusting the pH to 3-3.5 with acetic acid, and reacting at 85-90°C for 4-6 hours to obtain a modified furfural resin; (2) adding 6-9 wt% of phosphoric acid and 3-5 wt% of nano powder to the modified furfural resin to uniformly mix the modified furfural resin to obtain a composite resin; The composite resin impregnation pressure is 2-4 MPa, and the impregnation time is 4-6 hours; the composite resin curing temperature after impregnation is 180-220°C, and the curing time is 2 hours; the secondary high-temperature heat treatment temperature is 1800-2300°C, and the time is 1-3 hours; The apparent density of the composite material blank is 1.25-1.45 g / cm 3 .
4. The method for preparing the high temperature resistant carbon / ceramic gradient composite brake pad according to claim 3, characterized in that: The nanometer powder is a compound of nanometer carbide powder and nanometer silicon powder in a weight ratio of (2-3):1; the nanometer carbide powder is one or both of silicon carbide powder and zirconium carbide powder.
5. The method for preparing the high temperature resistant carbon / ceramic gradient composite brake pad according to claim 2, characterized in that: The specific operation of directional reactive infiltration is as follows: spread and compact the silicon powder infiltration material on the bottom of the graphite crucible, place the composite material blank on top of the infiltration material, heat it to 1800-2000°C under the protection of argon inert gas, and keep it warm for 1-3 hours to obtain a carbon / ceramic gradient composite material blank.
6. The method for preparing the high temperature resistant carbon / ceramic gradient composite brake pad according to claim 2, characterized in that: The volume density of the carbon / ceramic gradient composite friction plate is characterized by a gradient distribution, and the density near the infiltration composite area is 2.0-2.2g / cm 3 ; The density of the composite material area away from the infiltration material is 1.7-1.9g / cm 3 .
7. The method for preparing the high temperature resistant carbon / ceramic gradient composite brake pad according to claim 1, characterized in that: The composite material heat insulation sheet is a high-silicon composite material or a quartz fiber composite material.
8. A high temperature resistant carbon / ceramic gradient composite brake pad made according to the preparation method according to any one of claims 1 to 7.
9. An application of a high temperature resistant carbon / ceramic gradient composite brake pad prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Applicable to special vehicles, heavy-duty vehicles, sports cars and passenger cars equipped with carbon / ceramic brake discs.
Citation Information
Patent Citations
Carbon ceramic braking pad for high-speed train and preparation method of carbon ceramic braking pad
CN103511525A
Preparation method of low-wear automobile carbon / ceramic brake pad
CN112430110A
Aviation carbon ceramic brake material and preparation method thereof
CN117534494A
Method of making a short carbon fibre-reinforced silicon carbide composite material
EP1008569A1
Method of Producing Carbon Fiber Reinforced Ceramic Matrix Composites
US20080143005A1